THE DETECTION OF POLIOMYELITIS VIRUS IN FLIES COLLECTED DURING EPIDEMICS OF POLIOMYELITIS : II. CLINICAL CIRCUMSTANCES UNDER WHICH FLIES WERE COLLECTED - Trask, James D. (The Rockefeller University Press, 1943)
During the summer and fall of 1941, 19 samples of flies were collected in epidemic areas both during and after epidemics of poliomyelitis. Of 8 samples collected for the most part during the latter part of a local epidemic but within 10 days of the onset of a local case of poliomyelitis, 4 yielded the virus; whereas of 8 samples collected more than 10 days from the onset of the last local case, none yielded the virus. In 4 instances there was a potential (though not proven) source of virus (in the form of "exposed" human feces of recent origin) within a few yards or few feet of the site where fly collections were made. Collections of flies from 3 of these sites yielded the virus. No attempt is made in this paper to develop epidemiological implications from this finding.